CREATION OF WHEAT BRAN HYDROLYZATE PRODUCTION TECHNOLOGY (Scientific journal of the Fergana State University, 2023)
In our country, the raw materials used for the production of cosmetics, perfumes and household detergents are practically not produced, but are purchased abroad. As a result of this project proposed by our creative team, it is recommended to create and produce a technology for the production of wheat bran hydrolyzate, which is the main raw material for cosmetic products (shampoo, liquid soap, shower gels, creams for hands, face, body, lips, etc.) products .